Influence of warm rolling temperature on multi-scale lamellar structure and mechanical properties of medium carbon steel - Guolong Liu; Minghe Zhang; Yunli Feng; Kuo Cao; Shilei Li; Yandong Wang (Journal of Materials Research and Technology, 2022)
Improving the synergy between strength and ductility of medium carbon steel, a multi-scale lamellar structure was developed via hot water quenching and warm rolling at different temperatures. The multi-scale lamellar structure is composed of banded proeutectoid ferrite phase, fine equiaxed ferrite and cementite. The average sizes of subgrains and grains of warm rolled samples at 550 °C is 0.53 μm and 2.3 μm, respectively. When the rolling temperature went up, the fraction of HAGBs increased while the fraction of LAGBs decreased. It is found that the dislocations gradually localized from uniformity with increasing rolling temperature. When the rolling temperature was 650 °C, an obvious substructure was formed, and a large proportion of cementite was spheroidized. The best combination of strength and uniform elongation was obtained by rolling at 550 °C with tensile strength of about 1.2 GPa. In-situ high-energy X-ray study showed that the loads of ferrites with different orientations were similar in the elastic stage, and the stress distribution after yield was significantly different. It is considered that LAGBs strengthening accounts for more than 35%. The strengthening mechanism was verified by in-situ high energy X-ray, and the accuracy of multiscale-LAGBs strengthening theory was verified.